Protocol for the Sri Lankan Cerebral Palsy Register pilot study. Issue 8 (20th August 2020) - Heiyanthuduwage, Thilini Madushika; Sumanasena, Samanmali P; Kitnasamy, Gopi; Smithers Sheedy, Hayley; Khandaker, Gulam; Fernando, Romaniya; Wijesekara, Saraji; Jagoda, Jayatri; Ratnayake, Pyara; Wanigasinghe, Jithangi; Mclntyre, Sarah; Goldsmith, Shona; et al.
Abstract : Introduction: Cerebral palsy (CP) describes a heterogeneous group of motor disorders resulting from disturbance in the developing brain. CP occurs in approximately 2.1 per 1000 live births in high-income countries, but in low- and middle-income countries (LMICs) the prevalence and severity of CP may be greater and aetiological risk factors different. In Sri Lanka, a LMIC, there have been no epidemiological studies of CP to date. Systematically collected data are required to identify opportunities for primary and secondary prevention, to plan and establish services to support children and adults with CP and their families and to act as a sampling frame for new research. Here we describe a pilot study protocol for a CP register in Sri Lanka. Methods and analysis: The aim of this study is to establish a CP register in Sri Lanka. We will use different surveillance methodologies in two provinces of Sri Lanka: hospital and community surveillance in the Western Province and community surveillance in the Eastern Province. A common record form will collect demographic, clinical and service data for children with CP <18 years living in these two provinces. Data will be transferred to a secure online data repository and used to describe the epidemiology of CP in these regions. We will describe the strengths and challenges of the surveillance mechanisms and estimate the resources required for ongoing hospital and community based surveillance in the Western and Eastern provinces and to include additional provinces across the country. Ethics and dissemination: This study has ethical clearance from The University of Kelaniya, National Health Research Council, the Institutional Ethics Review Committee of the Lady Ridgeway Hospital, Colombo South Teaching Hospital and the Director of the North Colombo Teaching Hospital. Results from this research will be disseminated through local and international conferences and through publications in peer-reviewed journals.